2023
DOI: 10.1002/adfm.202300522
|View full text |Cite
|
Sign up to set email alerts
|

A Phase Engineering Strategy of Perovskite‐Type ZnSnO3:Nd for Boosting the Sonodynamic Therapy Performance

Abstract: The sensitization performance of sonosensitizers plays a key role in the sonodynamic therapy (SDT) effect. Herein, ZnSnO3:Nd nanoparticles with R3c phase/amorphous heterogeneous structure are developed by phase engineering strategy and applied as an ideal sonosensitizer. In the crystalline perovskite‐type ZnSnO3:Nd, the substitution of the Zn2+ with Nd3+ causes the O 2p non‐bonded state to move toward the Fermi level, which optimizes the band structure for ultrasound sensitization by reducing bandgap. Meanwhil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Our recent study revealed that ZnSnO 3 nanocubes are feasible SDT sensitizers; however, their therapeutic effect has been hindered by their insufficient piezoelectric performance. [20] Here, we found that ZnSnO 3 quantum dots (QDs) have good piezoelectric properties, and the related maximum effective piezoelectric coefficient (d 33 ) can reach 30.44 pm V −1 under a bias voltage from −10 to +10 V. Combining the semiconductor and optical properties, ZnSnO 3 QDs are potential SPDT sensitizers. However, their extremely small size (<5 nm) allows them to be easily engulfed by macrophages or eliminated from the body through the kidneys during transport.…”
Section: Introductionmentioning
confidence: 95%
“…Our recent study revealed that ZnSnO 3 nanocubes are feasible SDT sensitizers; however, their therapeutic effect has been hindered by their insufficient piezoelectric performance. [20] Here, we found that ZnSnO 3 quantum dots (QDs) have good piezoelectric properties, and the related maximum effective piezoelectric coefficient (d 33 ) can reach 30.44 pm V −1 under a bias voltage from −10 to +10 V. Combining the semiconductor and optical properties, ZnSnO 3 QDs are potential SPDT sensitizers. However, their extremely small size (<5 nm) allows them to be easily engulfed by macrophages or eliminated from the body through the kidneys during transport.…”
Section: Introductionmentioning
confidence: 95%
“…Ultrasound is a type of mechanical wave that has been extensively used in the medical field, especially in cancer diagnosis and therapy, owing to its noninvasiveness, minor energy attenuation, and high tissue‐penetration capability. [ 14–17 ] For instance, high‐intensity focused ultrasound is applied in the treatment of various tumors in the form of thermal ablation, which requires accurate localization to avoid hyperthermia as a side effect. Interestingly, low‐power ultrasound (1 MHz, 1–2 W cm ‐2 ) used in the medical field has the capability to produce some reactive oxygen species (ROS) that can react with certain prodrugs and release active drug molecules for chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in order to enhance the therapeutic efficiency of the formulation, appropriate therapeutic agents could be loaded into the NPs. Several investigations have been conducted on the biodegradability of nanomaterials in a biological milieu, demonstrating promising outcomes for instance in terms of therapeutic efficacy and release profiles (e.g., erosion-based release mechanisms). Curcumin (Cur), a natural polyphenolic compound, has been established as a promising drug in a variety of diseases. , Cur has powerful anti-inflammatory, antioxidant, and anticalcification properties; however, its clinical application is hindered by several drawbacks, including low aqueous solubility and rapid metabolism . Cur loading into PSI NPs not only addresses these limitations but also enables targeting of delivery of Cur to the disease site.…”
Section: Introductionmentioning
confidence: 99%